PRIMARY ECTOPIC PAPILLARY CARCINOMA OF THYROID IN THE LARYNX: AN UNUSUAL PRESENTATION - S Menon, Shalini; R, Balakrishnan; Valliathan, Manna (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Ectopic thyroid is the result of the failure of migration of thyroid along its tract from the floor of the primitive foregut to its final pretracheal position. The incidence of an ectopic lesion in adults is 7%. Most common location is the base of tongue (lingual). Other diverse sites are larynx, trachea, mediastinum, and pericardium. These ectopic tissues may develop the same diseases as the thyroid gland. Here, we report a case of a young female presenting with a foreign body sensation in the throat and on examination revealed a smooth submucosal swelling involving the supraglottis. The entire cyst was excised in toto by KTP 532 laser via an endolaryngeal approach and it was reported as papillary carcinoma of the thyroid. Literature search reported only a few cases of intralaryngeal ectopic thyroid and none with a papillary carcinoma of the larynx. This is the first reported case of papillary carcinoma of thyroid in the larynx.